Stock Market Reactions and Cybersuits in the United States - Chan, Wen Li (2005)
The internet has heralded much change in the landscape in which business interact with each other. To sustain the competitive of their organizations in the digital age, managers need to be aware of the impact of cybersuits on the shareholder wealth of their corporations. Using the event study methodology, and in particular the non-parametric rank test proposed by Corrado (1989) for excess returns in stock prices in event studies, this study analyses the reactions of the stock to announcements of filings, settlements and judgments in cybersuits, as well as announcements of the issuance of subpoenas to Internet service providers. A proposed classification of cybersuits into intellectual property, privacy and security, cases on commercial aspects of cyberlaw, and other cases, is used to categorize the cybersuits studied. the data collection for this study was carried out via a comprehensive full-text search of the archives of the reports contained in the Wall Street Journal over a 10-year period from 1995 through to 2005 to obtain a compilation of cybersuits whereby at least one party, whether plaintiff ar defendant, was a publicly-listed corporation in the US. From the data collected, it was found that the nature of the cybersuits filed ove the past decade generally followed the evolution of key milestones in legislation, trend or new technologies related to the internet. In respect of the event study findings, consistent with previous studies, plaintiff companies were found to be able to, and did, cause damage to defendant companies through the filing of cybersuits. Interestingly, the market was in fact found to have rewarded plaintiffs, in addition to causing defendants to suffer significant negative abnormal returns, upon the filing of cybersuits on intellectual property matters, an observation indicative of an increased awareness amongst investor regarding the value of intellectual capital in business. The negative reaction of the market to news of both plaintiffs and defendants in settlements of cybersuits indicated that investors preferred to have outcomes of cybersuits determined by the courts rather than being settled amongst parties, in a bid for greater legal certainty in the application of the law to Internet-related issues. Evidence from findings on defendants in cybersuit judgments showed that market participants viewed legal certainty to be imperative in privacy and security cases. finally, despite existing tensions between First Amendment rights and "John Doe" subpoena procedures, investors appeared to support measures to unmask anonymous Internet miscreants in order for aggrieved companies to have legal recourse against posters of cybersmear. Lastly, proposed trading rules which required action on news of filings, settlements or judgments, as well as correct anticipation of such incidences, offered some opportunity for profit.